Genuine Smiles by Patients During Marital Interactions are Associated with Better Caregiver Mental Health. (27th January 2018) - Lwi, Sandy J; Casey, James J; Verstaen, Alice; Connelly, Dyan E; Merrilees, Jennifer; Levenson, Robert W
Abstract: Objective: Providing care for a spouse with dementia is associated with an increased risk for poor mental health. To determine whether this vulnerability in caregivers is related to the expression of positive emotion, we examined 57 patients with Alzheimer's disease and behavioral variant frontotemporal dementia and their spouses as they discussed a marital conflict. Method: Facial behavior during the discussion was objectively coded to identify Duchenne (i.e., genuine) smiles and non-Duchenne (i.e., polite) smiles. Caregiver mental health was measured using the Medical Outcomes Survey. Results: Greater expression of Duchenne smiles by patients was associated with better caregiver mental health, even when accounting for covariates (i.e., diagnosis, patient cognitive functioning, and caregiver marital satisfaction). Greater expression of non-Duchenne smiles by patients was associated with worse caregiver health, but only when covariates were entered in the model. Expression of Duchenne and non-Duchenne smiles by caregivers was not associated with caregiver mental health. Discussion: Patients' expression of Duchenne and non-Duchenne smiles may reveal important aspects of the emotional quality of the patient–caregiver relationship that influence caregiver burden and mental health.